2016
DOI: 10.1186/s12864-016-3122-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals regulators of the response to PDGF-BB treatment in pulmonary artery smooth muscle cells

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a lethal disease with pronounced narrowing of pulmonary vessels due to abnormal cell proliferation. The platelet-derived growth factor BB (PDGF-BB) is well known as a potent mitogen for smooth muscle cell proliferation. To better understand how this growth factor regulates pulmonary arterial smooth muscle cells (PASMCs) proliferation, we sought to characterize the response to PDGF-BB stimulation at system-wide levels, including the transcriptome and proteome.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
(57 reference statements)
0
26
1
Order By: Relevance
“…Downregulation of BMPRII protein reduces the expression of Id1 gene, which further promotes PASMC proliferation [37,38]. Recent study has demonstrated that PDGF inhibits BMPRII/ Id1 signaling and thus promotes PASMC proliferation [39]. It has been shown that miR-21 reduces BMPRII protein by directly targeting BMPRII mRNA, promotes PASMC proliferation and further regulates pulmonary vascular remodeling [5,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of BMPRII protein reduces the expression of Id1 gene, which further promotes PASMC proliferation [37,38]. Recent study has demonstrated that PDGF inhibits BMPRII/ Id1 signaling and thus promotes PASMC proliferation [39]. It has been shown that miR-21 reduces BMPRII protein by directly targeting BMPRII mRNA, promotes PASMC proliferation and further regulates pulmonary vascular remodeling [5,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐339 is one of the differentially expressed miRNAs reported in our previous work (Chen et al. ). In this study, miR‐339 was found to be downregulated not only by PDGF‐BB, but also by many other cytokines and growth factors, including FGF2, ET‐1, ANG II, and so forth.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, we have identified 13 miRNAs that were differentially expressed in rat PASMC (RPASMC) in response to PDGF‐BB stimulation (Chen et al. ). The expression level of these miRNAs were measured in different organs of the rat and one miRNA, miR‐339, was found to be relatively highly expressed in the arteries, compared to most other organs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations